Arabic Language Curriculum Development in Ma’had Umar Bin Al-Khattab Surabaya in Maintaining Middle Eastern Culture-based Educational Institutions.: Pengembangan Kurikulum Bahasa Arab di Ma’had Umar Bin Al-Khattab Surabaya Dalam Mempertahankan Lembaga Pendidikan Berbasis Kultur Timur Tengah. - Luthfi Ans; Budi Haryanto (Academia Open, 2021)
Ma’had Umar Bin Al-Khattab Surabaya is an educational institution that concentrates on providing Arabic language education and islamic studies with an institutional style based on Middle Eastern Culture. This study aims to describe and analyze the development of the Arabic language curriculum and the achievement of Arabic curriculum development at MUBK Surabaya in maintaining Middle Eastern culture based educational institutions.This research uses a naturalistic qualitative approach with the type of field research and case study research design. The subjects in this study were Mudir, Deputy Mudir, Lecturers of Ma’had, alumni and students of MUBK Surabaya. data was collected by observation, interview, and documentation. Data analiysis techniques using data analysis techniques of Miles and Huberman, namely data reduction, data presentation, and drawing conclusions.The results of this research showed that the development of the Arabic language curriculum at MUBK Surabaya was carried out because of many background aspect including: stakeholder demands and students need. The principles of curriculum development are relevance, flexibility, continuity, as well as effectiveness and efficiency. The foundation of curriculum development used is religious, capability, psychological, and sosio-cultural. Middle Eastern culture at MUBK Surabaya includes 3 aspects, namely: first, the value system and nature of Middle Eastern people thought. Second, the pattern of life, attitudes, and Islamic habits of the Middle East. Third: patterns of student-teacher relationships in Middle Eastern cultures. The acvievement of curricilum development at MUBK Surabaya is by designing several courses to support the implementation of the 3 aspects of Middle Eastern culture. Keywords : Arabic Language Curriculum Development; Educational Institutions; Middle East Culture.